2012
DOI: 10.1159/000342785
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Development of Nucleus Taeniae of the Amygdala

Abstract: The avian nucleus taeniae of the amygdala (TnA) corresponds to part of the mammalian medial amygdala. Like its mammalian counterpart, it has been shown to be involved in the control of social function. According to behavioral observations, such control is already necessary early in the ontogenetic development of a bird. If so, TnA should be one of the earliest differentiating brain structures of the telencephalon. Our anatomical study shows that TnA can already be delineated at posthatching day one. The volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 111 publications
0
14
0
Order By: Relevance
“…Deficits in the control of social behaviors were also observed in studies using male songbirds [Cheng et al, 1999;Ikebuchi et al, 2009]. Evidence from these hodological and behavioral studies combined with the results of immunohistochemical studies [Balthazart et al, 1992[Balthazart et al, , 1998Yamamoto et al, 2005] supports the view that the TnA corresponds to the mammalian medial amygdala [Reiner et al, 2004] and is involved in the control of both sexual and social behaviors [Cheng et al, 1999;Svec et al, 2009;Ikebuchi et al, 2009Ikebuchi et al, , 2013.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…Deficits in the control of social behaviors were also observed in studies using male songbirds [Cheng et al, 1999;Ikebuchi et al, 2009]. Evidence from these hodological and behavioral studies combined with the results of immunohistochemical studies [Balthazart et al, 1992[Balthazart et al, , 1998Yamamoto et al, 2005] supports the view that the TnA corresponds to the mammalian medial amygdala [Reiner et al, 2004] and is involved in the control of both sexual and social behaviors [Cheng et al, 1999;Svec et al, 2009;Ikebuchi et al, 2009Ikebuchi et al, , 2013.…”
mentioning
confidence: 55%
“…In an anatomical study that investigated the development of the TnA in zebra finches, it was shown that this nucleus can already be delineated after hatch day 1 and that its growth precedes that of the song nuclei [Ikebuchi et al, 2013]. As the authors suggested in the paper, the possibility that the TnA plays a role in promoting social interaction with a tutor should be tested because this interaction is important for facilitation of learning.…”
Section: Possible Role Of Motivation In Song Learningmentioning
confidence: 99%
“…However, in the Avian Brain Nomenclature Forum it became evident that only a rostromedial part of the so-called nucleus taeniae may be comparable to the medial amygdala of other vertebrates, which is primarily a subpallial structure (Reiner et al 2004a). Moreover, the nucleus taeniae identified in zebra finches (Ikebuchi et al 2013) does not appear to correspond to the subpallial nucleus taeniae recognized by the nomenclature forum as the likely homolog of the mammalian medial amygdala (Reiner et al 2004a), since such nucleus in zebra finches is located within the arcopallium. A similar situation applies to the nucleus taeniae identified in budgerigars (Roberts et al 2002).…”
Section: Medial Extended Amygdala (Eame)mentioning
confidence: 99%
“…This structure corresponds to what Reiner et al (2004a) (Avian Brain Nomenclature Forum) called the subpallial division of nucleus taeniae. Since this name is also used to refer to a pallial nucleus (Puelles et al 2007; Ikebuchi et al 2009, 2013), to avoid confusion, in the present study we adopted the nomenclature of Abellán and Medina (2009) regarding the avian medial extended amygdalar structures (see next paragraph). In particular, we are using the term subpallial medial amygdala (MeAs) or just medial amygdala (MeA) to refer to the nucleus rich in Nkx2.1, Lhx6 and Shh expressing cells, which are comparable to the pallidal and preoptic cellular components of the medial amygdala of mammals (Abellán and Medina 2009).…”
Section: Medial Extended Amygdala (Eame)mentioning
confidence: 99%
See 1 more Smart Citation